Effect of randomization of nasal high flow rate in preterm infants. Issue 9 (8th July 2019) - Hough, Judith L.; Shearman, Andrew D.; Jardine, Luke; Caldararo, Deborah; Schibler, Andreas
Abstract: Objective: To assess the effect of nasal high flow (NHF) cannula on end‐expiratory level (EEL), continuous distending pressure (CDP) and regional ventilation distribution in preterm infants. Design: A prospective observational clinical study with randomly applied NHF rates. Patients and Setting: Preterm infants requiring continuous positive airway pressure (CPAP) respiratory support in a Neonatal Intensive Care Unit. Interventions: Infants were measured on randomly applied flow rates at 2, 4, and 6 L/min of NHF and compared with bubble CPAP. Measurements and Results: Regional ventilation distribution and EEL were measured using electrical impedance tomography (EIT) and respiratory inductance plethysmography (RIP) in 24 preterm infants (31.19 ± 1.17 weeks corrected age). Changes in CDP were measured from the esophagus via the nasogastric tube. Physiological variables were also recorded. There were no differences in ventilation distribution, EEL or CDP between CPAP and NHF ( P  > .05). However, the physiological variables of FiO2 ( P  = .01) and SpO2 /FiO2 ( P  < .01) were improved on CPAP compared with NHF. Conclusion: NHF applied in random order with flow rates between 2 to 6 L/min was equally as good as CPAP in maintaining EEL and ventilation distribution in stable preterm infants. Overall oxygenation was better on CPAP compared to NHF.